On the use and disadvantage of heroes for the nation - Tom Verschaffel (Studies on National Movements, 2015)
The third volume of Studies on National Movements is devoted to the role(s) of heroes and hero narratives in national movements. In his introduction, Tom Verschaffel traces the importance and the versatility of the theme.